2019
DOI: 10.3390/jcs3030084
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Hydrogels Crosslinked by Genipin and Reinforced with Cellulose Nanocrystals: Production and Characterization

Abstract: In this work, chitosan hydrogels crosslinked with genipin and reinforced with cellulose nanocrystals (CNC) were developed and characterized with the aim of future biomedical applications. CNC was produced by acid hydrolysis and characterized by atomic force microscopy (AFM). Chitosan/CNC nanocomposite hydrogels were produced with different CNC concentrations (w/w): 0%, 2%, 4%, and 6%. The genipin was used as a crosslinking agent in a genipin/chitosan molar proportion of 1:8. The hydrogels were characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…The impact of the presence of NPs in polymeric matrix on the porosity and swelling degree was already discussed by other authors. Recently, in the work of Pomari et al 30 increased rigidity and low swelling degree of chitosan hydrogel were afforded by increasing the content of cellulose nanocrystals into the polymeric matrix. Similarly, Montanheiro et al 25 reported on the PHBV scaffolds of low porosity produced by the addition of cellulose nanocrystals.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the presence of NPs in polymeric matrix on the porosity and swelling degree was already discussed by other authors. Recently, in the work of Pomari et al 30 increased rigidity and low swelling degree of chitosan hydrogel were afforded by increasing the content of cellulose nanocrystals into the polymeric matrix. Similarly, Montanheiro et al 25 reported on the PHBV scaffolds of low porosity produced by the addition of cellulose nanocrystals.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the DOI: 10.15259/PCACD. 25.001 use of a low genipin concentration produced well-crosslinked hydrogels. The swelling of crosslinked hydrogels depended strongly on the degree of crosslinking and the pH of the medium.…”
Section: Chemically Crosslinked Hydrogelsmentioning
confidence: 99%
“…Pomari et al focused on pre-treatment in an ultrasonic bath (5 min, room temperature) before mixing the solutions and for a short crosslinking time (1 min) when preparing crosslinked hydrogels from chitosan (MW 190-310 kDa, weight, DD 75-85%) and genipin (8:1 molar ratio) in an aqueous solution of acetic acid (1%) [25]. Crosslinked chitosan hydrogels were then formed at room temperature for 7 days in plastic tubes, where contact was limited to the surface hydrogel with the atmosphere (О 2 ), as suggested by another study [26].…”
Section: Chemically Crosslinked Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations